Complexation leaching of critical and strategic metals from nickel converter slag using organic acids - Lim, Bona; Alorro, Richard; Aylmore, Mark; Grimsey, D. (2023)
Nickel converter slag is a waste product formed during the converting process in nickel production. In recent times the processing of nickel converter slag has gained attention as a secondary source of cobalt (Co) and nickel (Ni). Nickel and cobalt are considered critical and strategic metals that are essential for nations’ economy and defence, as well as high-technology industry. In particular, Co and Ni can be utilised in the batteries, superalloys, and automobiles. Extraction of critical and strategic metals from slag can be categorised as technospheric mining. In this study, the slag was characterised using combination of XRF, XRD, ICP-OES, FESEM and TIMA for better understanding of deportment of Ni and Co and texture of Ni converter (CV) slag. Complexation leaching by using a combination of citric acid and EDTA was undertaken to extraction by using the leaching agent and complexing agent. The preliminary test showed the most promising result. The leaching experiment was carried out with various parameters such as the reagent concentration, temperature, particle size, and pulp density. The optimum condition for extracting Co and Ni from CV slag is following; citric acid 1 M, EDTA 0.3 M, 80 °C, 6 hr, pulp density 2.5% (w/v), − 75 μm and 250 rpm, which recovered 85.29% of Co and 59.85% of Ni.